Analisa Terhadap Pelaksanaan Kewenangan Penyidikan Badan Narkotika Nasional Dalam Tindak Pidana Narkotika Di Kabupaten Gayo Lues - Bahri, Samsul; Iskandar, Hadi; Badar, Zainal Abidin (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2023)
This study aims to examine the implementation of the authority of the Gayo Lues Regency National Narcotics Agency in processing narcotics crimes, the form of coordination between Gayo Lues Regency National Narcotics Agency investigators and Gayo Lues Regency Police Investigators, the obstacles and efforts faced by Gayo Regency National Narcotics Agency investigators. Lues in carrying out his authority to investigate narcotics crimes. Based on the research results, it is known that the implementation of the investigative authority of the Gayo Lues Regency National Narcotics Agency is carried out based on Law Number 35 of 2009 concerning Narcotics. The form of coordination between the Gayo Lues Regency National Narcotics Agency and the Gayo Lues Regency Police Investigators is if they are going to conduct a joint raid and conduct outreach to agencies, villages/villages, make arrests and determine whether the suspect should be rehabilitated by BNN or not, then notify each other in writing that start of investigation. The obstacles faced by investigators from the Gayo Lues Regency National Narcotics Agency in implementing their authority to investigate narcotics crimes are lack of community participation, the public is still unfamiliar with the regulations on narcotics abuse, and personnel limitations. maximize the capabilities of existing personnel, and try to request additional personnel from the Police.